Clinical Effectiveness of Precooling Agent (Ice) and Topical Anesthetic Gel in Reduction of Pain Before the Intraoral Anesthetic Injection in Children—A Systematic Review and Meta-analysis - Nilam V Honaje; Nupur S Ninawe; Ritesh R Kalaskar; Avani R Doiphode; Shruti Balasubramanian; Suyash S Joshi (Dental Journal of Advance Studies)
Aim: Clinical effectiveness of precooling agent (ice) and topical anesthetic gel in reduction of pain before the intraoral anesthetic injection in children—a systematic review and meta-analysis. Background: Topical anesthesia plays a crucial role in pediatric dentistry to mitigate the discomfort and anxiety associated with local anesthesia injections. Numerous strategies have been investigated to minimize pain perception during injections. In this systematic review, the focus is on comparing the efficacy of application of local anesthetic gel and cooling the injection site with ice. Materials and methods: Research question: Are precooling agent (ice) more effective than topical anesthetic gel (Benzocaine or lidocaine) in reduction of pain before the intraoral anesthetic injection in children? Research protocol: This systematic review followed the recommendation of PRISMA guideline 2020. Literature search: An electronic search of the databases was performed to find the effectiveness of precooling agent (ice) and topical anesthetic gel (benzocaine and lidocaine) in reduction of pain before the intraoral anesthetic injection in children aged between 5 and 10 years. Data extraction: Authors independently extracted the data from the eight included studies based on the inclusion criteria. Quality appraisal: The risk of bias was assessed using a tool developed by the Cochrane Collaboration for randomized clinical trial studies. Results and interpretation of results: After conducting a search, 305 published studies were identified. Following the elimination of duplicate studies and a thorough analysis of full-text articles, a total of eight studies were chosen for inclusion in the systematic review. Conclusion: Precooling the soft tissues with topical ice proved to be more effective in significantly reducing pain perception in children compared with the use of topical anesthetic gel. Clinical significance: It is important for pediatric dentist to know appropriate use of precooling agent. This paper gives an insight into appropriate use of precooling agent ice for reduction of pain during intraoral anesthetic injection in children.